PROBLEMATIKA ASAS RETROAKTIF DALAM HUKUM PIDANA INDONESIA - Raharjo, Agus (Jurnal Dinamika Hukum, 2008)
One of the fundamental principles of criminal law is the principle of legality. This principle of prohibition enforcement consequences subsided (non-retroactive) a criminal law. In its development, this principle was deviation, especially for the crimes that fall into that category gross human rights violations. Constitutional Court decision to cancel the implementation regulation No. subsided. Law No. 2/2002 or Law No. 16/2003 closed the possibility of other criminal regulations made retroactive. Retroactive provisions of the (retroactive) in Indonesia is only possible for the gross human rights violations as defined in Law No. 39/1999 or Law No. 26/2000. This issue becomes complicated when the crime occurred a new type will cause a lot of casualties but no criminal laws that govern them. Will restrictions on retroactive application of the principle is so tight to let the victim fall. Kata Kunci: asas legalitas, asas retroaktif, asas non-retroaktif.